2017
DOI: 10.1136/bmjdrc-2016-000320
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the FreeStyle Libre Flash glucose monitoring system in patients with type 1 and 2 diabetes mellitus

Abstract: ObjectiveTo evaluate the performance of the FreeStyle Libre Flash continuous glucose monitoring (FSL-CGM) system against established central laboratory methods.Research design and methods20 subjects (8 type 1 diabetes mellitus, 12 type 2 diabetes mellitus) were analyzed. FSL-CGM sensor measurements (inserted in arm and abdomen) were compared with capillary blood glucose results analyzed with StatStrip as semigold standard. The glucose response after a standardized oral glucose load was measured by FSL-CGM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
140
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 28 publications
(23 reference statements)
21
140
3
3
Order By: Relevance
“…It has been shown that in lower glucose ranges and during hypoglycaemia, CGM devices are less accurate [34, 38, 39] and results are usually expressed as MAD. When the capillary BG values were < 70 mg/dL, the MAD in our study was 13.7 mg/dL, which is comparable with the findings of other studies reporting MAD values between 12.3 and 13.4 mg/dL [20, 35, 37]. Hence, it remains of utmost importance to confirm sensor-reported hypoglycaemia or impending hypoglycaemia by capillary BG control.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…It has been shown that in lower glucose ranges and during hypoglycaemia, CGM devices are less accurate [34, 38, 39] and results are usually expressed as MAD. When the capillary BG values were < 70 mg/dL, the MAD in our study was 13.7 mg/dL, which is comparable with the findings of other studies reporting MAD values between 12.3 and 13.4 mg/dL [20, 35, 37]. Hence, it remains of utmost importance to confirm sensor-reported hypoglycaemia or impending hypoglycaemia by capillary BG control.…”
Section: Discussionsupporting
confidence: 80%
“…Szadkowska et al [27] studied the FGM in 78 children and found that 99.1% of the results fell in zone A and B. In adults, Baily et al [20], found 99.7% and Fokkert et al [35] found 99.8% of the results in zone A and B. It is noteworthy to mention that Edge et al [25] and Baily et al [20] compared the scanned SG values with the capillary BG levels determined by the build-in meter using FreeStyle Optium test strips.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, 75-g OGTT resulted in a slower rise in glucose level as determined by FGM than that obtained by the perchloric acid hexokinase method, POC testing, test strip, and conventional CGM during the first 45-60 minutes after glucose loading [11]. Moreover, a study using CGM including FGM for type 1 diabetes patients indicated that all sensors performed less accurately during hypoglycemia and best during hyperglycemia [12].…”
Section: Disclosurementioning
confidence: 99%